Cultura de aprendizagem no setor de serviços profissionais: um estudo em empresas contábeis - Silva Júnior, José Aurélio da (2024)
Based on organizational challenges, accounting service companies are embedded in an environment filled with changes in legislation. To overcome the challenges inherent in this context, a learning culture can be an effective strategy to be used. This study aims to understand the learning culture in accounting companies based on the theoretical model of learning culture investigation by Marsick and Watkins (2003). Aligned with this research delimitation, this study aims to investigate the learning culture in accounting companies. The study has a qualitative approach, with field research and a descriptive and exploratory objective, involving 14 employees working in accounting firms established in the city of Fortaleza/CE. For data collection, a semi-structured interview script was used based on the theoretical model of Marsick and Watkins (2003). In the data analysis, content analysis was performed, supported by the Atlas.ti software. The results practically describe how the learning culture occurs at the individual, group, and organizational levels. The results at the individual level occur with learning at work, with support and encouragement for continuous training, growth opportunities, challenges, and errors for learning extraction, and feedback. The results at the group level were discussed through team learning, which occurred through group discussions. The results at the organizational level occur with the dissemination of learning, learning mechanisms, and mechanisms for capturing improvement points, contributing to the organization's vision, departmental integration, individual work perception, and through professional recognition, with the support of organizational culture, leadership training, leadership training and guidance, and internal information sharing. The limitations of the research relate to the unavailability of accounting companies to adhere to the research. Future research can be carried out by combining different theoretical models of learning culture, as well as combining qualitative methodological procedures.